Mismatches between extended urbanization and everyday socioenvironmental conflicts in Santarém, Pará, Brazil - Duarte Cardoso, Ana Cláudia; Diniz Oliveira, Kamila; do Vale Gomes Pinho, Taynara (Sustainability in Debate, 2020)
This article discusses how Global North environmental concerns would be applicable to the contemporary Global South urbanization - a zone of overexploitation of natural resources and imposition of homogenizing spatial patterns. The brand-new Metropolitan Region of Santarém (MRS), located in the Brazilian Amazon, is taken as a case study to demonstrate that reeditions of power and social hierarchy result in institutional violence and creation of an extensive urban tissue, where original occupation and spatial structures linked to the production of commodities for export co-exist. MRS demands the understanding of Global North and South connections and also of city and rural linkages to allow the understanding of a new urban that encompasses it all.